Incidental Treatment of a Subclinical Chronic Tension-Type Headache by Cosmetic Use of Botulinum Toxin A: A Case Report - Iselin Saltvig; Steen Henrik Matzen (Karger Publishers, 2017)
Background: Headache is a common disorder of the nervous system; chronic headache in particular may affect quality of life negatively. The pathophysiology is multifactorial and not completely elucidated. Studies have demonstrated the beneficial effects of botulinum toxin A on chronic migraine headaches, but failed to show the same effect on chronic tension-type headaches. Methods: We present the case of a 32-year-old woman who after receiving cosmetic injections with botulinum toxin A for fine lines of the forehead experienced relief of subclinical tension-type headaches. Conclusions: Although the effect of botulinum toxin A on chronic tension-type headaches is limited, several studies demonstrate its pain-modulating effects, and as such it is worth paying attention to this potential beneficial effect when performing cosmetic injections with botulinum toxin A.